2019
DOI: 10.1007/s12192-019-00979-z
|View full text |Cite
|
Sign up to set email alerts
|

Small heat shock proteins: multifaceted proteins with important implications for life

Abstract: Small Heat Shock Proteins (sHSPs) evolved early in the history of life; they are present in archaea, bacteria, and eukaryota. sHSPs belong to the superfamily of molecular chaperones: they are components of the cellular protein quality control machinery and are thought to act as the first line of defense against conditions that endanger the cellular proteome. In plants, sHSPs protect cells against abiotic stresses, providing innovative targets for sustainable agricultural production. In humans, sHSPs (also know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
69
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 131 publications
0
69
0
1
Order By: Relevance
“…We have previously shown that mutant human HSPB8 is prone to aggregation in patient fibroblasts (Irobi et al 2012). However, there is so far no clear consensus on how these aggregates contribute to the neurodegeneration (Adriaenssens et al 2017;Carra et al 2019). Regarding the molecular compensation, it is a principle that is frequently observed within the class of the sHSPs (Carra et al 2019).…”
Section: Hspb8mentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that mutant human HSPB8 is prone to aggregation in patient fibroblasts (Irobi et al 2012). However, there is so far no clear consensus on how these aggregates contribute to the neurodegeneration (Adriaenssens et al 2017;Carra et al 2019). Regarding the molecular compensation, it is a principle that is frequently observed within the class of the sHSPs (Carra et al 2019).…”
Section: Hspb8mentioning
confidence: 99%
“…However, there is so far no clear consensus on how these aggregates contribute to the neurodegeneration (Adriaenssens et al 2017;Carra et al 2019). Regarding the molecular compensation, it is a principle that is frequently observed within the class of the sHSPs (Carra et al 2019). For instance, multiple sHSPs were shown to bind BAG3 (BCL2-associated athanogene 3; the main binding partner of HSPB8), of which HSPB8 has the highest affinity (Fuchs et al 2009;Hishiya et al 2011;Morelli et al 2017a).…”
Section: Hspb8mentioning
confidence: 99%
“…Efficient PQC requires the interplay of the different chaperone systems [2,3]. Some of these, e.g., the HSPA (Hsp70) family, consume ATP for client-binding cycles, whereas others, such as the small heat shock proteins (HSPB), are energy-independent [1,4]. Cochaperones such as J-domain proteins (JDP, Hsp40) and BAG proteins assist chaperones in their functions, mediate interactions of the different chaperone families, and affect the fate of the client proteins [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…the Hsp60 chaperonins GroEL and TRiC, and the Hsp90 and Hsp70 families, ATP binding and/or hydrolysis promotes conformational changes that facilitate the folding and/or release of their clients 1,2,4,5,6,7,8 . However, some chaperones are not dependent on energy from nucleotide binding/hydrolysis, and instead their intrinsic structural flexibility is proposed to be key to their function 3,9,10,11,12 . The functional mechanisms of these ATP-independent chaperones, including how they bind and release their substrates in a controlled manner, is generally not well understood.…”
Section: Introductionmentioning
confidence: 99%